Assessment of targeted and non-targeted responses in cells deficient in ATM function following exposure to low and high dose X-rays. - Anne Kiuru; Meerit Kämäräinen; Sirpa Heinävaara; Katri Pylkäs; Kim Chapman; Armi Koivistoinen; Teuvo Parviainen; Robert Winqvist; Munira Kadhim; Virpi Launonen; Carita Lindholm (PLoS ONE)
Radiation sensitivity at low and high dose exposure to X-rays was investigated by means of chromosomal aberration (CA) analysis in heterozygous ATM mutation carrier and A-T patient (biallelic ATM mutation) lymphoblastoid cell lines (LCLs). Targeted and non-targeted responses to acutely delivered irradiation were examined by applying a co-culture system that enables study of both directly irradiated cells and medium-mediated bystander effects in the same experimental setting. No indication of radiation hypersensitivity was observed at doses of 0.01 Gy or 0.1 Gy for the ATM mutation carrier LCL. The A-T patient cells also did not show low-dose response. There was significant increase in unstable CA yields for both ATM mutation carrier and A-T LCLs at 1 and 2 Gy, the A-T cells displaying more distinct dose dependency. Both chromosome and chromatid type aberrations were induced at an increased rate in the irradiated A-T cells, whereas for ATM carrier cells, only unstable chromosomal aberrations were increased above the level observed in the wild type cell line. No bystander effect could be demonstrated in any of the cell lines or doses applied. Characteristics typical for the A-T cell line were detected, i.e., high baseline frequency of CA that increased with dose. In addition, dose-dependent loss of cell viability was observed. In conclusion, CA analysis did not demonstrate low-dose (≤100 mGy) radiosensitivity in ATM mutation carrier cells or A-T patient cells. However, both cell lines showed increased radiosensitivity at high dose exposure.